2012
DOI: 10.1016/j.freeradbiomed.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Porphyrin, MnTE-2-PyP5+, Acts as a Pro-Oxidant to Potentiate Glucocorticoid-Induced Apoptosis in Lymphoma Cells

Abstract: Using current chemotherapy protocols, over 55% of lymphoma patients fail treatment. Novel agents are needed to improve lymphoma survival. The manganese porphyrin, MnTE-2-PyP5+, augments glucocorticoid-induced apoptosis in WEHI7.2 murine thymic lymphoma cells, suggesting that it may have potential as a lymphoma therapeutic. However, the mechanism by which MnTE-2-PyP5+ potentiates glucocorticoid-induced apoptosis is unknown. Previously, we showed that glucocorticoid treatment increases the steady state levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
161
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(166 citation statements)
references
References 40 publications
(63 reference statements)
4
161
1
Order By: Relevance
“…In turn, this further supports the likelihood of the wide range of the reactivities of SOD mimics. We and others reported thus far on such reactivities (2,4,8,9). Yet, these reports have still made only modest impact on the field of Redox Biology and Drug Design.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In turn, this further supports the likelihood of the wide range of the reactivities of SOD mimics. We and others reported thus far on such reactivities (2,4,8,9). Yet, these reports have still made only modest impact on the field of Redox Biology and Drug Design.…”
mentioning
confidence: 78%
“…Second, the experimental data show the differential impact of MnPs on normal versus cancer cells, which we understand now to be due to their differential redox environment: the cancer cell appears to be under high oxidative stress and produces higher peroxide levels that redox-active drugs can employ, as shown in lymphoma and leukemia studies by the Tome's group, to modify protein thiols and greatly affect proliferative and apoptotic processes. Eventually, such action would kill a cancer cell (7,8). At low levels of peroxide, the transient inhibition of NF-jB DNA binding would reduce secondary oxidative stress and, in turn, heal the normal cell, as indicated in Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of caspase-3, caspase-8 and caspase-9 were determined by measuring cleavage of the Ac-DEVD-pNA (caspase-3 substrate), Ac-IETD-pNA (caspase-8 substrate) and Ac-LEHD-pNA (caspase-9 substrate) to pNA using the detection kits (Beyotime, Nantong, China) as described previously [46,47]. The caspase activity in the samples was quantified with a Microplate reader (Thermo, Waltham, USA) at 405 nm.…”
Section: Measurement Of Caspasesmentioning
confidence: 99%
“…We mentioned earlier that Mn-SOD is protective against pancreatic cancer. Mn-SOD expression was also found to be anomalously low in erythrocytes of patients suffering from NHL [235]. In vitro studies have shown that an Mn-SOD mimetic had an anti-proliferation effect on human NHL Raji cells [236].…”
Section: Non-hodgkin's Lymphomamentioning
confidence: 97%